The Dose-Response Effect of the Mast Cell Stabilizer Ketotifen Fumarate on Posttraumatic Joint Contracture: An in Vivo Study in a Rabbit Model. Issue 1 (January 2021) - Schneider, Prism S.; Johal, Herman; Befus, A. Dean; Salo, Paul T.; Hart, David A.; Hildebrand, Kevin A.
Abstract : Background: Posttraumatic joint contracture is a debilitating complication following an acute fracture or intra-articular injury that can lead to loss of motion and an inability to complete activities of daily living. In prior studies using an established in vivo model, we found that ketotifen fumarate (KF), a mast cell stabilizer, was associated with a significant reduction in the severity of posttraumatic joint contracture. Our primary research question in the current study was to determine whether a dose-response relationship exists between KF and posttraumatic joint contracture reduction. Methods: A standardized operative method to create posttraumatic joint contracture in a knee was performed on skeletally mature New Zealand White rabbits. The animals were randomly assigned to 1 of 5 groups (n = 10 per group): a nonoperative control group, an operative control group, or 1 of 3 experimental KF groups (0.01 mg/kg [the KF 0.01 group], 0.1 mg/kg [KF 0.1], or 5.0 mg/kg [KF 5.0]). Flexion contractures were measured following 8 weeks of knee immobilization using a hydraulic material-testing machine. The posterior knee joint capsules were then harvested for quantification of myofibroblast and mast cell numbers with immunohistochemistry analysis. Results: Forty-five rabbits were used in the final analysis. Contracture severity was significantly reduced in the KF 0.1 group (p = 0.016) and the KF 5.0 group (p = 0.001) compared with the operative control group. When converted to a percent response, posttraumatic joint contracture reduction was 13%, 45%, and 63% for the KF 0.01, KF 0.1, and KF 5.0 groups, respectively. A half-maximal effective concentration (EC50 ) for KF of 0.22 mg/kg was established. There was also a decrease in myofibroblasts, mast cells, and substance P-containing nerve fiber counts with increasing doses of KF. Conclusions: Using a preclinical, rabbit in vivo model of posttraumatic joint contracture, increasing doses of KF were associated with decreasing biomechanical estimates of knee posttraumatic joint contracture as well as decreasing numbers of myofibroblasts, mast cells, and substance P-containing nerve fibers. Clinical Relevance: KF has been used safely in humans for more than 40 years and, to our knowledge, is the first and only agent ready to be potentially translated into an effective treatment for posttraumatic joint contracture.